Profile of Multisystem Inflammatory Syndrome in Children related to COVID-19: A Multicentric Study from South India - Sagar Bhattad; Ramya Sadashiva; Rachna S Mohite; Karthik Arigela; Syed M Naushad; Jeeson Unni; Rajappan Pillai; Gladys Cyril; George Paul; Suresh Kumar; Sathish Kumar; Manjula Anand; et al. (Pediatric Infectious Disease)
Multisystem inflammatory syndrome in children (MIS-C) is a severe complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection associated with significant morbidity and can be fatal if left unrecognized. A retrospective multicentric study was carried out at five tertiary care centers in South India, to evaluate the clinical profile of children admitted with MIS-C associated with SARS-CoV-2 infection. Cases of MIS-C diagnosed during October 2020 to December 2021 were included. Diagnosis of MIS-C was based on World Health Organization (WHO) criteria. All children underwent echocardiography at admission, discharge, and 4–6 weeks of follow-up. Children with MIS-C were treated with intravenous immunoglobulin (IVIG) and/or steroids. We compared younger children (<5 years of age) with older ones to determine if age at presentation could predict severity in children with MIS-C. A total of 81 children were diagnosed to have MIS-C during the study period. The mean age of presentation was 6.8 years. Around 29.6% of the children had a shock at admission and 54.3% had myocardial dysfunction. The average duration of a pediatric intensive care unit (PICU) stay was 6.6 days. Anti-SARS-CoV-2 antibodies were found to be positive in 75.3% of patients. Children with high N-terminal prohormone of brain natriuretic peptide (NT-proBNP) had more severe presentations. All children responded promptly to IVIG and steroids and the mortality was 0%. No difference was noted in terms of outcome between younger (<5 years) and older children. A significant proportion of children with MIS-C present with shock and myocardial dysfunction. Anti-SARS-CoV-2 antibodies were positive in 75% of children whose primary infection went unnoticed. We hereby report one of the largest cohorts of MIS-C patients from the Indian subcontinent.